Longitudinal management of a patient with severe pulmonary hypertension undergoing complex noncardiac surgery – a study detailing successful, multidisciplinary care. (December 2020) - Wackerle, H. Douglas; Cobert, Julien; Dunkman, W. Jonathan
Abstract: Patients with pulmonary hypertension (PH) are known to be at increased risk for perioperative complications, and require extensive preoperative optimization, strict intraoperative management, and involved postoperative care. This study describes the perioperative care of a patient with severe PH undergoing jaw surgery which required the transition of combination therapy oral (PO) PH medications throughout the phases of care. We present this as a framework for how anesthesiologists can drive multidisciplinary planning to minimize risk in these complex patients and produce a successful outcome.